Trends and changes in paediatric tonsil surgery in Sweden 1987–2013: a population-based cohort study. Issue 1 (13th January 2017) - Borgström, Anna; Nerfeldt, Pia; Friberg, Danielle; Sunnergren, Ola; Stalfors, Joacim
Abstract : Objectives: The objective of this study was to longitudinally describe the history of tonsil surgery in Swedish children and adolescents regarding incidence, indications for surgery, surgical methods and the age and gender distributions. Setting: A retrospective longitudinal population-based cohort study based on register data from the Swedish National Patient Register (NPR) and population data from Statistics Sweden. Participants: All Swedish children 1–<18 years registered in the NPR with a tonsil surgery procedure 1987–2013. Results: 167 894 tonsil surgeries were registered in the NPR 1987–2013. An increase in the total incidence rate was observed, from 22/10 000 person years in 1987 to 47/10 000 in 2013. The most marked increase was noted in children 1–3 years of age, increasing from 17 to 73/10 000 person years over the period. The proportion children with obstructive/sleep disordered breathing (SDB) indications increased from 42.4% in 1987 to 73.6% in 2013. Partial tonsillectomy, tonsillotomy (TT), increased since 1996 and in 2013 55.1% of all tonsil procedures were TTs. Conclusions: There have been considerable changes in clinical practice for tonsil surgery in Swedish children over the past few decades. Overall, a doubling in the total incidence rate was observed. This increase consisted mainly of an increase in surgical procedures due to obstructive/SDB indications, particularly among the youngest age group (1–3 years old). TT has gradually replaced tonsillectomy as the predominant method for tonsil surgery.